Equilibrium, kinetic and thermodynamic study of pesticides removal from water using novel glucamine-calix[4]arene functionalized magnetic graphene oxide. Issue 4 (14th March 2019) - Nodeh, Hamid Rashidi; Kamboh, Muhammad Afzal; Wan Ibrahim, Wan Aini; Jume, Binta Hadi; Sereshti, Hassan; Sanagi, Mohd Marsin
Abstract : New nanocomposite composed of Fe3 O4, graphene oxide and meglumine functionalized with calix[4]arene successfully used for pesticides removal. Abstract : A novel nanocomposite of MGO-NGC, composed of magnetic Fe3 O4 nanoparticles (M), graphene oxide (GO), and N -methyl-d -glucamine functionalized calix[4]arene (NGC), was synthesized and applied as an effective adsorbent for the removal of two selected pesticides, namely hexaconazole and chlorpyrifos from water samples. The adsorbent was characterized by FTIR, SEM, EDX, TEM, and XRD. The main parameters affecting the adsorption process such as adsorbent dosage, pH of sample solution, salt effect, pesticide concentration, and adsorption time were investigated. The data from kinetic studies fitted well to the pseudo-second order kinetic model with R 2 > 0.99. Among the isotherm models of Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich, the Langmuir isotherm fitted well to the adsorption process and demonstrated the monolayer adsorption pattern of the pesticides. Moreover, high adsorption capacities of 78.74 and 93.46 mg g −1 were obtained for chlorpyrifos and hexaconazole, respectively. Thermodynamic and free energy data indicated the physisorption mechanism for the adsorption process. The new adsorbent can be employed as an efficient, environment friendly, and highly reusable alternative for the removal of chlorinated pesticides from aqueous media.